Imagery: image structure, different approaches to imagery - Duvlaeva Nozigul Xolmuxammat qizi (Genius Journals, 2023)
The article focuses on one of the generic text categories of fictional texts is imagery. It gives thorough information about 6 main types (visual, auditory, olfactory, gustatory, tactile, and kinesthetic) of imagery and approach to the notion in broad and narrow sense. Furthermore, image referent (object to which a linguistic expression refers), image agent (reflected object) and image basis (common features which arise from the principle of similarity) are have also been discussed in the article.
Keywords: visual; auditory; olfactory; gustatory